KAJIAN ETNOBOTANI OBAT TRADISIONAL DAN PEMANFAATANNYA OLEH MASYARAKAT SUKU KUTAI DI DESA JAMBUK, PENAWAI DAN MUARA KEDANG, KECAMATAN BONGAN, KABUPATEN KUTAI BARAT - Putri, Fiorhentina; Hendra, Medi; Susanto, Dwi (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
This research aims to determine the types of medicinal plants used by the tribal communities of Kutai, herb medicine, the way to processing of medicinal plants and the environment unit of medicinal plants. The method used is descriptive methods, Participatory Ethnobotanical Appraisal technique, interviews and snow ball and also transect walk systematic sampling. Data analysis using Ms Excel 2013.Has been found as many as 113 kinds of medicinal plants, for which 109 species are from 53 families and 4 other species are not identified. Potion used as many 38 types of potions. Medicinal plants was processed with crushed/mashed 51 species; boiled 43 species; use directly 13 species; kneaded 12 species; marinated/brewed 5 species; made the statue 3 species, slice 2 species; dried, squeezed, shredded, torn and plaited each of them 1 species. The most environment unit of medicinal plants was found in the yard (73%), groves or simpung (11%), stall 5%, not obtained 4%, the curb 4% and in the riverside (3%).